Inventarisasi Tanaman Obat yang Dapat Digunakan sebagai Elemen Lansekap pada Dataran Rendah hingga Dataran Tinggi Di Kabupaten Tabanan - WARDANA, WAYAN WISNU; ASTAWA, I NYOMAN GEDE; SARDIANA, I KETUT (Jurnal Arsitektur Lansekap, 2015)
ABSTRACT   Inventory of Medical Plants used as Landscape Elements From the Lowlands to the Highlands of Tabanan Regency   Tabanan regency is one district that has lowland and highland. Besides, Tabanan still very strong Balinese culture that is still many people who use medical plants not only as a raw material cuisine, but also as an infrastructure for prayer, ritual raw materials, and also as a treatment for balian , but these plants also have beautiful stem, leaves, flowers, and fruits so it can be used as an ornamental plant or as landscape elements, especially at home, in hotels and government offices. Results from this study can be useful for people who want to know the medical plants in the area of the Tabanan regency and the suitability of areas where the growth is suitable in highland or lowland areas. Methods used in this study are literature studies, surveys, observation and identification (observation), survey using list name of plants and data analysis. Research conducted in three sub-districts such as Kediri, Marga, and Baturiti. Results indicated that, based on the altitude there was found several number of medical plants species i.e. in sub-districts of Kediri 43 species, in sub-districts of Marga 26 species, and in sub-districts of Baturiti 15 species. Medical plants in the area usually found in the garden, telajakan , or in tegalan land unit.   Keywords: landscape elements, medical plants, Tabanan regency